PENGARUH PENDIDIKAN DAN PELATIHAN SERTA KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI PADA KANTOR KEJAKSAAN NEGERI PALU SULAWESI TENGAH - HASLINDA, HASLINDA (Fakultas Ekonomi Universitas Tadulako, 2015)
This study aims to determine the influencet of education and training as well as emotional intelligence on the performance of employees at the State Attorney Office of Palu, Central Sulawesi. Sample consists of 31 people, who were selected with census method. Model of analysis multiple linear regressions with SPSS computer program for Windows Release 22.0. The research concludes that education and training (X1) and emotional intelligence (X2) simultaneously have significant influence on employee performance (Y) in Attorney Office of Palu. This is evidenced by the F test that shows the significance value below 0.05 of 0.000. Education and training (X1) partially has significant influence on employee performance (Y); this is evidenced by the t-test that shows significance value below 0.05, of 0.001. Emotional intelligence (X2) partially has significant influence on employee performance (Y), which is evidenced by the t-test that shows significance value below 0.05 of 0.000.